Вычислите:[latex]1) \sqrt{31-6 \sqrt{26} } - \sqrt{31+6 \sqrt{26} } 2) \sqrt[3]{5 \sqrt{2}-7 } * \sqrt{3+2 \sqrt{2} } [/latex]

Вычислите: [latex]1) \sqrt{31-6 \sqrt{26} } - \sqrt{31+6 \sqrt{26} } 2) \sqrt[3]{5 \sqrt{2}-7 } * \sqrt{3+2 \sqrt{2} } [/latex]
Гость
Ответ(ы) на вопрос:
Гость
[latex]1. \sqrt{31-6\sqrt{13}}-\sqrt{31+6\sqrt{13}}=\sqrt{ (\sqrt{18}- \sqrt{13})^2 }-\sqrt{ (\sqrt{18}+ \sqrt{13})^2 }=\\ \sqrt{18}- \sqrt{13}-\sqrt{18}- \sqrt{13}=-2 \sqrt{13} ;\\ 2. \sqrt[3]{5 \sqrt{2}-7 } * \sqrt{3+2 \sqrt{2} } = \sqrt[3]{( \sqrt{2}-1 )^3}* \sqrt{( \sqrt{2}+1 )^2}=\\ (\sqrt{2}-1)(\sqrt{2}+1)=1; [/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы